2022
DOI: 10.1002/biot.202100698
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9‐mediated knockout of a prolyl‐4‐hydroxylase subfamily in Nicotiana benthamiana using DsRed2 for plant selection

Abstract: The properties of host plants used for molecular farming can be modified by CRISPR/Cas9 genome editing to improve the quality and yield of recombinant proteins. However, it is often necessary to target multiple genes simultaneously, particularly when using host plants with large and complex genomes. This is the case for Nicotiana benthamiana, an allotetraploid relative of tobacco frequently used for transient protein expression. A multiplex genome editing system incorporating the DsRed2 fluorescent marker for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…However, functional compensation apart from transcriptional upregulation is also considerable since all p4h genes are expressed in protonema under standard growth conditions. A possible rebalancing effect by the remaining P4Hs was also reported after a quadruple KO of the Nicotiana P4H4 subset, where the KO led to a reduced abundance of the unmodified version of the hinge region from a recombinant IgA1 antibody and to an increased fraction of peptides O -glycosylated with pentoses (Uetz et al, 2022). In our data, the abundance of the prolyl-hydroxylated form of the peptide GANYAITFCPTVTPVAK was strongly reduced in the P4H5 KO line, indicating that in this case loss of P4H5 is hardly compensated.…”
Section: Discussionmentioning
confidence: 77%
“…However, functional compensation apart from transcriptional upregulation is also considerable since all p4h genes are expressed in protonema under standard growth conditions. A possible rebalancing effect by the remaining P4Hs was also reported after a quadruple KO of the Nicotiana P4H4 subset, where the KO led to a reduced abundance of the unmodified version of the hinge region from a recombinant IgA1 antibody and to an increased fraction of peptides O -glycosylated with pentoses (Uetz et al, 2022). In our data, the abundance of the prolyl-hydroxylated form of the peptide GANYAITFCPTVTPVAK was strongly reduced in the P4H5 KO line, indicating that in this case loss of P4H5 is hardly compensated.…”
Section: Discussionmentioning
confidence: 77%
“…The remarkable fact now is that apparently, the sites of mucin-type O-glycosylation of mammalian proteins are also the sites prone to be modified by prolyl-4-hydroxylase and then by arabinosyl-transferase as exemplified by human erythropoietin expressed in the moss P. patens [38] or human IgA1 [39]. Hardly surprising, the same holds true for N. benthamiana with the only, albeit technologically relevant difference, that several prolyl-4-hydroxylase are redundantly at work in vascular plants [39,40], whereas knock-out of just one paralogous gene sufficed to suppress erythropoietin oxidation in P. patens [41].…”
Section: A Mosses Idea On O-glycosylationmentioning
confidence: 99%
“…Their endogenous N- and O-glycosylation patterns differ from humans, which has hampered the broad application of the expression system to produce human therapeutics ( Strasser et al, 2021 ). While there has been considerable effort in glycoengineering popular expression hosts such as Nicotiana benthamiana , N. tabacum , tobacco BY2 cells and the moss Physcomitrella patens towards humanized- and customized N-glycosylation ( Bakker et al, 2001 ; Koprivova et al, 2004 ; Strasser et al, 2008 ; Kallolimath et al, 2016 ; Limkul et al, 2016 ; Mercx et al, 2017 ; Jansing et al, 2019 ; Bohlender et al, 2020 ; Herman et al, 2021 ; Göritzer et al, 2022 ; Kogelmann et al, 2023 ) limited attention was cast towards modulating the plant endogenous O-glycosylation pathway ( Castilho et al, 2012 ; Yang et al, 2012 ; Parsons et al, 2013 ; Dicker et al, 2016 ; Ramírez-Alanis et al, 2018 ; Mócsai et al, 2021 ; Uetz et al, 2022 ). Plant-endogenous HyP and further modifications with pentoses (arabinoses) were found in several recombinantly produced proteins such as IgA1, MUC1, EPO-Fc, and Ara h 2 ( Karnoup et al, 2005 ; Weise et al, 2007 ; Pinkhasov et al, 2011 ; Castilho et al, 2012 ; Yang et al, 2012 ; Üzülmez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several P4H members from Arabidopsis thaliana , tobacco, and Solanum lycopersicum have been identified and characterized ( Yuasa et al, 2005 ; Kalaitzis et al, 2010 ; Velasquez et al, 2011 ). This paved the way for the discovery of similar enzymes in plant species utilized in plant molecular farming, such as N. benthamiana or P. patens ( Parsons et al, 2013 ; Mócsai et al, 2021 ; Uetz et al, 2022 ). While CRISPR/Cas9-mediated knockout of the P4H4 subfamily in N. benthamiana resulted in a noticeable change of the O-glycosylation pattern in the hinge region of a recombinant IgA1 antibody, the presence of considerable amounts of HyP residues suggested that other P4H enzymes are mainly responsible for proline oxidation in the IgA1 hinge region ( Uetz et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%